PENGARUH PENYEBARAN INFORMASI BERBASIS TIKTOK, PERCEIVED GREEN VALUE DAN NORMA SUBJEKTIF TERHADAP NIAT THRIFTING GENERASI MILENIAL - Ayu Andriani Simatupang; Nada Fathimah Nursaffanah; Dewi Kurniaty (Jurnal Bina Bangsa Ekonomika, 2024)
The results of this research illustrate the influence of TikTok-based information dissemination by the Millennial Generation on their concern for perceived green value and subjective norms, which can impact intentions to buy used goods (thrifting) both online and offline. Therefore, the quantitative method used in conducting this research involved distributing questionnaires to 115 respondents over a period of 30 days. This study examined two variables: independent variables including TikTok Social Media Information Distribution, Perceived Green Value, Subjective Norms, and the dependent variable, Green Purchase Intention